THE FUTURE OF HINDU ALUKTA IN TANA TORAJA POST-INTEGRATION WITH THE HINDU RELIGION - Segara, I Nyoman Yoga (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2023)
This research is based on the current situation after many Aluk Todolo believers were integrated with Hinduism. Over time, this integration experienced many obstacles and challenges. The new name resulting from integration, namely Hindu Alukta, does not eliminate the stigma and stereotypes associated with local religion and adherents of animism. To examine the future challenges that they face after integrating with Hinduism, this research uses qualitative methods with an in-depth interview technique with key informants, direct observation at the location, and the study of documents from various existing sources. Employing the Practice Theory framework from Bourdieu, this study found that the challenge that Hindu Alukta adherents faced is largely capital (which sourced from structural supports). This is because structurally, the government, in this case the Ministry of Religious Affairs, especially the Directorate General of Hindu Community Guidance, has not been able to serve and guide them optimally. The Ministry of Religious Affairs of the Province of South Sulawesi, especially the Hindu Community Advisors are not capable enough to provide post-integration services and guidance. Culturally, those are rooted from the local belief of Aluk Todolo, experienced struggles as adherents of the official religion (Hinduism).